Identification of cervical radiculo-myelopathy using Distribution of F-Latency (DFL), a new nerve conduction parameter (Bangladesh Journal of Medical Physics, 2015)
Distribution of F-latency (DFL) is a new nerve conduction parameter conceived and developed at Dhaka University which appears to have the ability to detect cervical radiculo-myelopathy early. The present work was taken up to evaluate its performance against diagnosis made using MRI on 24 median nerves of 12 patients reporting cervical radiculo-myelopathy at the Singapore General Hospital. Predictive analyses were carried out using contingency tables to evaluate the classification ability of DFL as against MRI as the standard. For the first analysis only double peaks or distinct broad peaks of DFL were assumed to indicate pathology. However, the sensitivity and accuracy could be improved significantly through redefining a broad peak as the pattern where the frequency of occurrence of a bin adjacent to the peak was greater than one third of the peak value, which was shown by a second analysis. A third analysis was also performed where a case of sensori-motor neuropathy, not identified as radiculo-myelopathy by MRI, was also included as an abnormality. This gave 88% accuracy (correct prediction) and 90% sensitivity. The rather low specificity value, at 67%, was due to the fact that the number of negative cases in the study group was small (5 out of 24). DFL has the potential of identifying cervical radiculo-myelopathy besides certain other peripheral neuropathy and may be used as a first line diagnostic or screening technique.Bangladesh Journal of Medical Physics Vol.7 No.1 2014 34-45